Serotonin 5-HT2A receptor activity mediates adipocyte differentiation through control of adipogenic gene expression - Bangning Yu (Nature Portfolio, 2021)
Abstract Serotonin 5-HT2 receptors are expressed in many tissues and play important roles in biological processes. Although the 5-HT2A receptor is primarily known for its role in central nervous system, it is also expressed in peripheral tissues. We have found that 5-HT2A receptor antagonists inhibit human subcutaneous primary adipocyte differentiation. We also show that siRNA knockdown of the 5-HT2A receptor blocks differentiation. Using gene expression analysis in combination with receptor antagonists we found that activity of 5-HT2A receptors is necessary very early in the differentiation process to mediate expression of adipogenic genes, including peroxisome proliferator-activated receptor gamma (ppar-γ), adipocyte protein 2 (aP2), adiponectin, and serine/threonine-protein kinase 1 (sgk1). We show here for the first time that 5-HT2A receptor activity is necessary for differentiation of human primary subcutaneous preadipocytes to adipocytes, and that 5-HT2A receptor activity mediates key genes related to adipogenesis during this process. Importantly, this work contributes to a greater understanding of the adipocyte differentiation process, as well as to the role of 5-HT2A receptors in peripheral tissues, and may be relevant to the development of novel therapeutic strategies targeting this receptor for the treatment of obesity related diseases.